Smallpox vaccination‐elicited antibodies cross‐neutralize 2022‐Monkeypox virus Clade II. Issue 3 (15th March 2023) - Criscuolo, Elena; Giuliani, Benedetta; Ferrarese, Roberto; Ferrari, Davide; Locatelli, Massimo; Clementi, Massimo; Mancini, Nicasio; Clementi, Nicola
Abstract: Since early May 2022, some monkeypox virus (MPXV) infections have been reported from countries where the disease is not endemic. Within 2 months, the number of patients has increased extensively, becoming the most considerable MPXV outbreak described. Smallpox vaccines demonstrated high efficacy against MPXVs in the past and are considered a crucial outbreak control measure. However, viruses isolated during the current outbreak carry distinct genetic variations, and the cross‐neutralizing capability of antibodies remains to be assessed. Here we report that serum antibodies elicited by first‐generation smallpox vaccines can neutralize the current MPXV more than 40 years after vaccine administration.